Parametric study on the bimetallic waveguide coupled surface plasmon resonance sensors in comparison with other configurations - Lee, Kyeong-Seok; Lee, Taek Sung; Kim, Inho; Kim, Won Mok (IOP PUBLISHING LTD, 2013)
In this study, a theoretical parametric study on the bimetallic waveguide coupled surface plasmon (SP) resonance sensors was presented in comparison with other alternative configurations suggested to achieve a high sensing resolution. The increasing ratio of inner Ag to outer Au was found to have more drastic effect on the enhancement in the SPR curve sharpness and the sensing resolution in response to the changes in bulk and thin analytes. It was confirmed that the effect of Ag to Au ratio was incomparably superior to that observed in a simple Au/Ag bimetal approach. Remarkably, our calculation also indicated that the sensing resolution could be comparable to that of long range SP resonance configuration and even better for the detection of thin analytes as the Ag to Au ratio increased to 3.75. In addition, the great flexibility in materials selection for the dielectric waveguide and the periodic generation of waveguide coupled modes were verified and their effects were discussed.
Keywords: THIN-FILM; ENHANCEMENT; BIOSENSORS; CHIPS